PHOTIUS’ ENCYCLICAL TO THE EASTERN PATRIARCHS THE PROJECT OF THEA NTI-LATIN POLEMICS - T. HAINTHALER (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2011)
The article deals with one of the key texts written in the genre of the anti-Latin polemics, Patriarch of Constantinople Photius’ Encyclical to the Eastern Patriarchs. The author discusses in detail all the items of the Photius’ Encyclical and demonstrates main trends and historical background of the document. The analysis comes to an end with the detection of the certain text’s tradition which formed when it was appealed to by later polemists with the Roman Church.